ASUHAN KEBIDANAN KOMPREHENSIF DENGAN KOMPLEMENTER PADA NY. “L” DI BIDAN PRAKTIK MANDIRI NY. “Y” DESA SUMBERMULYO KECAMATAN JOGOROTO KABUPATEN JOMBANG - Nadhira Ariviona; Ardiyanti Hidayah; Siti Nur Farida (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Introduction: In a person's life cycle, pregnancy, childbirth, postpartum, newborn, and pregnancy are physiological events, but there are several hazards or conditions that can endanger the mother and newborn, and can even cause death. One indicator of the development of health status is maternal and infant mortality, which is used to evaluate the success of health services and other health development programs. Objectives: The aim of midwifery care is to reduce the incidence of maternal and infant mortality. Methods: Midwifery care in the third trimester of pregnancy for Mrs. "L" was carried out starting at 37 weeks' gestation, 3 antenatal visits were made and there were no complications. in Mrs. "L" 40 weeks' labor at BPM Ny. "Y", normal delivery. By. Mrs "L" was born a term neonate at 40 weeks' gestation. At the time of baby care aged 6 hours, the baby's condition was healthy and there were no complications. Results: The results of midwifery care at Mrs. L pointed out that there is no difference between field and theoretical treatments. Officers have done what must be done. Conclusion: The conclusions and suggestions for writing this final project report are expected to be able to improve the quality of midwifery services provided according to the latest midwifery service standards according to midwife competencies.